Uveal Melanoma UK National Guidelines. Issue 16 (November 2015) - Nathan, P.; Cohen, V.; Coupland, S.; Curtis, K.; Damato, B.; Evans, J.; Fenwick, S.; Kirkpatrick, L.; Li, O.; Marshall, E.; McGuirk, K.; Ottensmeier, C.; et al.
Abstract The United Kingdom (UK) uveal melanoma guideline development group used an evidence based systematic approach (Scottish Intercollegiate Guidelines Network (SIGN)) to make recommendations in key areas of uncertainty in the field including: the use and effectiveness of new technologies for prognostication, the appropriate pathway for the surveillance of patients following treatment for primary uveal melanoma, the use and effectiveness of new technologies in the treatment of hepatic recurrence and the use of systemic treatments. The guidelines were sent for international peer review and have been accredited by NICE. A summary of key recommendations is presented. The full documents are available on the Melanoma Focus website.